Clinical evaluation of implant survival based on size and site of placement: A retrospective study of immediate implants at single rooted teeth sites - Sundar Ramalingam; Maryam Al-Hindi; Raniah Abdullah Al-Eid; Nasser Nooh (Elsevier, 2015)
Objectives: This retrospective clinical study sought to evaluate the survival of immediate implants placed at maxillary and mandibular single-rooted tooth extraction sites and to determine the relationship among implant size, placement site, and implant survival. Methods: Between January 2010 and June 2011, 85 patients (33 males, 52 females; mean age: 45 years) underwent immediate implant placement after extraction of single-rooted teeth. All implants were restored between 12 and 14 weeks after implant placement. The implant survival and its relationship with implant size and implantation site were evaluated by odds ratios (ORs). Results: Implants were placed at the following sites: upper central incisor (UCI, n = 35), upper lateral incisor (ULI, n = 27), upper second premolar (U2ndP, n = 36), lower incisor (LI, n = 53), and lower premolar (LP, n = 22). Implants of the following sizes were used: 5 × 10 mm (n = 24), 5 × 8 mm (n = 21), 4.3 × 10 mm (n = 77), 4.3 × 8 mm (n = 36), 3.5 × 10 mm (n = 12), and 3.5 × 8 mm (n = 3). After a mean follow-up time of 47 months, the overall implant survival rate was 96%. Survival rate was highest at the LI site (98.1%) and lowest at the ULI site (92.6%). All of the 5-mm implants survived (100%), as did most of the 4.3 × 10 mm implants (96.1%). Implants of 4.3 × 8 mm and 3.5 × 10 mm were the least successful (91.7%). Mandibular implants had a better survival rate (97.3%) than maxillary implants (94.9%). There was no significant OR of increased survival for any particular implant size or site. Conclusions: Immediate implant placement in fresh extraction sockets can give predictable clinical outcomes, regardless of the implant size and site of placement. Keywords: Immediate implants, Dental implants, Implant survival, Osseointegration, Implant site, Implant size